Catheter ablation and cognitive function in atrial fibrillation: A systematic review and meta-analysis - Chen, Pengfei; Chen, Zhuhong; Pan, Deng; Miao, Lina; Shi, Yujiao; Guo, Ming; Du, Jianpeng (Frontiers in Neurology, 2022)
Background: Atrial fibrillation (AF) is a risk factor for cognitive dysfunction. Although catheter ablation (CA) is one of the main treatments of AF, whether it can improve the cognitive function in patients with AF remains unclear. we conducted a systematic review and meta-analysis to evaluate the cognitive outcomes post-CA procedure. Methods: Two investigators independently searched the PubMed, EMBASE, Web of Science, CNKI, WanFang, and VIP databases from inception to September 2021 for all the potentially eligible studies. The outcomes of interests included dementia or cognitive disorder through scoring or recognized classification criteria. Heterogeneity was determined by the Cochrane's Q test and calculating the I2. A random-effect model was used to incorporate the potential effects of heterogeneity. Result: Thirteen studies including 40868 patients were included, among which 12086 patients received AF ablation. Meta-analysis indicated that AF ablation patients had a lower risk of dementia incidence in comparison to AF patients without ablation [Hazard Ratio (HR): 0.60, 95% CI: 0.43 to 0.84, p=0.003 I2=40%]. Significant differences were observed in the incidence of new-onset dementia [Risk Ratio (RR): 0.43, 95% CI: 0.28 to 0.65, p<0.0001 I2=84%]; the changes in the Montreal Cognitive Assessment(MoCA) score [weighted mean difference (WMD): 1.00, 95% CI: 0.36 to 1.64, p<0.005 I2=0%] and Mini-Mental State Examination(MMSE) score [WMD: 0.98, 95% CI: 0.69 to 1.26, p<0.00001 I2=0%]. However, in subgroup analysis, we didn’t observe significant changes in MoCA score at <3 months [WMD :1.20, 95% CI: -0.19 to 2.58, p =0.09 I2 = 50%] and changes in cognitive function scores between the radiofrequency group and cryoballoon group [standard mean difference (SMD) :0.39, 95% CI: -0.47 to 1.24, p =0.38 I2 = 87%]. The NOS indicated that included studies were moderate to high quality, while the quality of evidence assessed by GRADE was low in 2 and very low in 2. Conclusions: We analyzed the related cognitive outcomes after AF ablation. In overall population, AF ablation had a positive trend for improving cognitive function at >3 months post-procedure. However, AF ablation might not be related to the improvement of cognitive function at < 3 months.